A student guide to clinical legal education and pro bono - Kerrigan, Kevin; Murray, Victoria (Houndmills, Basingstoke, Hampshire [England] : Palgrave MacMillan, 2011)
This is an authoritative and practical student guide to clinical legal education, a subject that plays an increasingly important role within UK law schools.
What is clinical legal education and pro bono? / Kevin Kerrigan -- Setting up a clinical legal education or pro bono project / Kevin Kerrigan -- Ethics and professional conduct in clinic and pro bono / Kevin Kerrigan -- Client funding / Paul McKeown -- Working with your supervisor and others / Judith Gowland and Paul McKeown -- Interviewing and advising / Paul McKeown -- Legal writing and drafting / Carol Boothby -- Practical legal research / Jonny Hall -- Organising and strategising / Caroline Foster -- Advocacy / Judith Gowland -- Presentations / Victoria Murray -- Reflection / Victoria Murray -- Assessment / Victoria Murray -- Clinic, pro bono and your career / Victoria Murray -- Resources.
Includes bibliographical references (p. 289-292) and index.
Keywords: Law -- Study and teaching (Clinical education) -- United Kingdom; Public interest law -- United Kingdom